Expression of Brain-Derived Neurotrophic Factor in the Brain of Depressed Mice: Systematic Literature Review - Nur Azizah AS; Lysa Veterini; Hafid Algristian; Hotimah Masdan Salim (Universitas Muhammadiyah Surabaya, 2021)
Chronic stress exposure plays a role as a risk factor for depression. In chronic stress, there is prunning of nerve cell dendrites so that depression becomes irreversible. Depression is caused by low serotonin (5-HT2) neurotransmitters in the postsynaptic cleft. Recent findings in experimental animals indicate that serotonergic preparations are required to increase serotonin levels in the synapse opening, thereby triggering the formation of new dendrites to make depression reversible. The different results when these preparations create resistance in cases of chronic depression and actually increase the risk of uncomfortable and even fatal side effects with long-term use. This Systematic Literature Review uses the PubMed and Google Scholar databases for the period 2015-2020. A total of 322 articles at the beginning of identification and those that met the inclusion criteria in this study were six articles. The results of data extraction showed that the depression condition caused by various stressors resulted in BDNF levels in the hippocampus decreased significantly by p≤0.005. Based on the literature study, it was concluded that in depressive conditions, BDNF levels in the brain decreased.